Influence of perfusable microvasculature on excitation-contraction coupling in IPSC-derived myocardium. (25th November 2020) - King, O; Cruz-Moreira, D; Kit-Anan, W; Sayed, A; Wang, B.X; Fourre, J; Randi, A.M; Rasponi, M; Terracciano, C.M
Abstract: : The myocardium is one of the most densely vascularised tissues in the body, with dynamic metabolic demand from beating cardiomyocytes (CM) necessitating an intimate relationship with microvasculature. Endothelial cells (EC) produce a diverse array of cardio-active factors which acutely and chronically modulate myocardial phenotype. Disruption of CM-EC signalling results in pathological remodelling, and ultimately organ failure. However, as physiologically relevant recapitulation of CM-EC interaction has been difficult to achieve in vitro, many molecular mechanisms governing their interaction remain poorly understood. To induce cardiac vasculogenesis in vitro, we have developed microfluidic chips which subject 3D hydrogel cultures to precisely controlled flow. We then co-cultured human cardiac microvascular ECs, human left ventricular fibroblasts (FB), and human induced pluripotent stem cell-derived cardiomyocytes for 5 days under a pro-vasculogenic protocol (0.5 ul/min flow rate, 50ng/ml VEGF, 100ng/ml Ang-1). Via live and fixed immunofluorescence microscopy, we observed spontaneous formation of a microvasculature network with a continuously open lumen embedded within beating myocardium. Simultaneous quantification of iPSC-CM contractility and perfused red blood cell velocity reveals biomimetic pulsatile flow profile within the microvasculature. To evaluate the influence of microvasculature on CM function, we incorporated CMs differentiated from stem cells with the genetically encoded calcium biosensor GCaMP6F. Compared to CM only control, vascularised preparations demonstrate significantly faster calcium transient time to peak (−11.5%, p=0.007) and time to 50% relaxation (−15%, p=0.01). Under static conditions and 1Hz electrical stimulation, presence of EC was associated with reduced iPSC-CM arrhythmia at baseline (p<0.0001) and during 1uM isoprenaline treatment (p=0.0003), while maintaining isoprenaline induced Ca2+ handling quickening. To the best of our knowledge, this work represents the first fully perfusable model of the myocardial microvasculature, and highlights the importance of EC regulatory influence on CM function. Further work aims to investigate underlying molecular mechanisms to provide therapeutically relevant insight into cardiac biology. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): British Heart Foundation